RUH, NAFS, AKAL, QOLB, FITRAH SEBAGAI POTENSI DALAM MEMBEKALI MANUSIA SEBAGAI ABDULLAH - Fatimah Az Zahrah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This paper discusses five basic human potentials from the perspective of Islamic educational psychology: the ruh (spirit), nafs (nafs), akal (reason), qolb (heart), and fitrah (natural disposition), as the primary foundation for realizing human beings as 'Abdullah (servants of Allah). These five potentials are integral aspects in the formation of a complete, balanced Islamic personality, and aim to bring humans closer to God. This approach emphasizes that Islamic education focuses not only on cognitive aspects but also on spiritual and moral ones. Through the integration of these potentials, students are guided to understand the purpose of their lives as a form of devotion to Allah SWT.